2018
DOI: 10.1007/s10120-018-0821-2
|View full text |Cite
|
Sign up to set email alerts
|

Tree nut, peanut, and peanut butter consumption and the risk of gastric and esophageal cancer subtypes: the Netherlands Cohort Study

Abstract: Background Nut consumption has been associated with reduced cancer-related mortality. However, it is unclear whether nut consumption also reduces the risk of esophageal and gastric cancer subtypes. We prospectively investigated the relationship of tree nut, peanut, and peanut butter intake with risk of esophageal squamous cell carcinoma (ESCC), esophageal adenocarcinoma (EAC), gastric cardia adenocarcinoma (GCA), and gastric non-cardia adenocarcinoma (GNCA) in the Netherlands Cohort Study. Methods In 1986, 120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…In women, nuts, whole grains, fish, and the MUFA:SFA ratio were important aMEDr components contributing to the non-significant inverse associations observed for GCA and GNCA risk. Inverse associations (not all significant) between esophageal and/or gastric cancer subtypes and intakes of nuts (ESCC and GNCA), vegetables (ESCC and EAC), and fruits (ESCC) were also documented in previous NLCS analyses [ 35 , 36 ]. In addition, high intakes of red (non-significant) and processed meats were associated with an increased ESCC risk in men [ 37 ].…”
Section: Discussionmentioning
confidence: 57%
“…In women, nuts, whole grains, fish, and the MUFA:SFA ratio were important aMEDr components contributing to the non-significant inverse associations observed for GCA and GNCA risk. Inverse associations (not all significant) between esophageal and/or gastric cancer subtypes and intakes of nuts (ESCC and GNCA), vegetables (ESCC and EAC), and fruits (ESCC) were also documented in previous NLCS analyses [ 35 , 36 ]. In addition, high intakes of red (non-significant) and processed meats were associated with an increased ESCC risk in men [ 37 ].…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies have found significant inverse associations between nut consumption and overall mortality [1,2,3,4,5,6,7,8,9,10,11,12,13,14] as well as between nut consumption and cardiovascular (CVD) disease [6,8,9,12,15] and multiple cancers including pancreatic [16], colorectal [17], esophageal squamous cell carcinoma [18] and gastric noncardiac adenocarcinoma [19,20]. A past review study on nut intake and mortality reported all-cause and common causes of mortality such as cardiovascular and cancer mortality [5].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies published in the last ten years have demonstrated the influence of nut consumption on cancer [91,92,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107] (Table 5). Despite the fact that, in the observational studies, no causality could be proven, there were still several obvious strengths: prospective design for the majority of the studies, large population size, high retention rates with long-term follow-up, and adjustments for a multitude of other potential risk factors.…”
Section: Association Between Nuts and Cancermentioning
confidence: 99%
“…Several studies indicated that patients in the highest tree nut and peanut-intake group compared to the lowest intake group at any point in time during the study period were: 40%, 25%, and 14% less likely to die from total cancer, gastric noncardia adenocarcinoma, and lung cancer, respectively [16,97,98]. Also, they were 46%, 45%, and 47% less likely to die from esophageal squamous cell carcinoma, estrogen receptor negative breast cancer, and estrogen-progesterone receptor breast cancer, respectively [100,102]. Subjects having at least two servings of nuts per week had 0.68 times the risk of pancreatic cancer compared with subjects having nuts never or almost never [93].…”
Section: Association Between Nuts and Cancermentioning
confidence: 99%